2-Aminophenones, a common precursor to N-aryl isatins and acridines endowed with bioactivities. Issue 15 (12th April 2018) - Brikci-Nigassa, Nahida Mokhtari; Bentabed-Ababsa, Ghenia; Erb, William; Chevallier, Floris; Picot, Laurent; Vitek, Lucille; Fleury, Audrey; Thiéry, Valérie; Souab, Mohamed; Robert, Thomas; Ruchaud, Sandrine; Bach, Stéphane; et al.
Abstract: Because N -arylation of isatin only worked with iodoferrocene (and in low yield), we employed N -arylation of 2-aminophenones and subsequent oxidative cyclization to access various N -arylated isatins. In the course of this work, we observed that N -arylation using 2-iodofuran, 2-iodobenzofuran and 2-iodobenzothiophene did not lead to the expected derivatives, but to (benzo)furo- and (benzo)thieno[2, 3- b ]quinolines. Separate cyclization was also performed under acidic conditions on 2-(arylamino)phenones in order to obtain acridines and related compounds. Most of the synthesized compounds were screened for their antiproliferative activity in A2058 melanoma cells, and against a panel of disease-relevant kinases such as mammalian CDK5/p25, PIM1, CLK1, DYRK1A, GSK3α/β, Haspin and leishmanial CK1. The biological results are reported. Graphical abstract: